2022
DOI: 10.1515/jpem-2022-0336
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating and behaviors among young Egyptians with type 1 diabetes: risk factors and comorbidities

Abstract: Objectives The study aimed to assess occurrence of eating disorders and its nature, associated risk factors, and comorbidities in a cohort of adolescents with type 1 diabetes (T1D). Methods In this cross-sectional study, 138 patients were recruited to complete three questionnaires for assessment of eating disorder (ED); Eating Attitude Test (EAT-26) and Eat Behavior questionnaire (ORTO-15) and Eating Disorder Examination Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…In the present study, 16.5% of the participants enrolled were positively screened for DEBs. This result is comparable with data collected by cross-sectional studies in children and adolescents with T1D from all over the world (17.4% for Egyptian [ 5 ], 25% for Turkish [ 6 ], 13.8% for Norwegian [ 7 ], 39.3% for Chinese [ 8 ], 30.1% for Greek [ 9 ], and 28.1% for Italian populations [ 4 ]). Results from this study are in line with what the available literature specifies around adolescence and T1D [ 31 ], meaning that this age is the most difficult in terms of psychosocial adjustment to the illness as well as correct adherence to therapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, 16.5% of the participants enrolled were positively screened for DEBs. This result is comparable with data collected by cross-sectional studies in children and adolescents with T1D from all over the world (17.4% for Egyptian [ 5 ], 25% for Turkish [ 6 ], 13.8% for Norwegian [ 7 ], 39.3% for Chinese [ 8 ], 30.1% for Greek [ 9 ], and 28.1% for Italian populations [ 4 ]). Results from this study are in line with what the available literature specifies around adolescence and T1D [ 31 ], meaning that this age is the most difficult in terms of psychosocial adjustment to the illness as well as correct adherence to therapy.…”
Section: Discussionsupporting
confidence: 85%
“…A recent Italian cross-sectional study of 690 adolescents with T1D estimated a DEB prevalence of 28.1% (21% boys, 35% girls) [ 4 ]. Similar results have been reported for other adolescent populations with T1D across the world [ 5 , 6 , 7 , 8 , 9 ]. A population-based study from national registers in Sweden and Demark investigated the within-individual association between T1D and eating disorders, highlighting a risk of 2% of developing a subsequent eating disorder in this population [ 10 ].…”
Section: Introductionsupporting
confidence: 89%
“…In this regard, and upon reviewing the existing literature from the Arab world, only minimal data are available. A recent study [ 23 ] on 138 young Egyptian patients with T1D found that 17.4% of the total sample scored positive for DEBs on the eating attitude test, while 32.6% scored positive for DEBs on the Eating Disorder Examination Questionnaire (EDE-Q6) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, malnutrition contributes to the deaths of around 20% of cancer patients, whereas in case of type 1 diabetes mellitus peripheral neuropathy, ketoacidosis, and microalbuminuria occur more frequently in individuals with orthorexia. 5,29 Early detection of ON and appropriate intervention are crucial to enhance the management of patients with chronic illnesses. Therefore, they should be assessed for the risk of developing this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with eating disorders were found to have a higher prevalence of peripheral neuropathy, ketoacidosis, and microalbuminuria. Episodes of hypoglycemia were more frequent among those with high EAT-26 and EDE-Q6 scores 29.…”
mentioning
confidence: 91%